Effect of HIIT on hemostasis and vascular stiffness: a systematic review and meta-analysis of randomized controlled trials - Jiao, Mingyue; Li, Qingmei; Xie, Xianzhi; Qiu, Zhen (Frontiers in Cardiovascular Medicine, 2025)
BackgroundSeveral small randomized trials have examined the effects of high-intensity interval training (HIIT) on hemostasis and vascular stiffness. However, a clear consensus regarding these effects has not been established. The study is to systematically review the evidence and quantify the impacts of HIIT compared with moderate-intensity continuous training (MICT) or usual care (UC) on hemostasis and vascular stiffness.MethodsRandomized controlled trials (RCTs) exploring the impact of HIIT, MICT, or UC on hemostasis and vascular stiffness were retrieved from PubMed, Embase, Web of Science, and Cochrane databases up to June 10, 2025. A meta-analysis was performed to compare the standardized mean differences (SMD) of changes from baseline to post-intervention in platelet count (PLT), fibrinogen (FIB), D-dimer (D-D), carotid-femoral pulse wave velocity (cfPWV), augmentation index (AIx), AIx normalized to a heart rate of 75 beats·min−1 (AIx@75HR), flow-mediated dilation (FMD), and brachial flow-mediated dilation normalized (nFMD), which were used to evaluate hemostasis and vascular stiffness. The 95% confidence interval (95% CI) was calculated along with the SMD. All analyses were conducted in R (version 4.3.3).ResultsOverall, 68 RCTs involving 2,679 patients were included in the analysis. PLT [SMD (95% CI) = −0.26 (−0.51; −0.01)] and FIB [SMD (95% CI) = −0.60 (−1.18; −0.01)] in hemostasis were decreased. Decreased cfPWV [SMD (95% CI) = −0.22 (−0.38; −0.06)], AIx [SMD (95% CI) = −0.16 (−0.30; −0.02)], and AIx@75HR [SMD (95% CI) = −0.35 (−0.61; −0.10)], as well as increased FMD [SMD (95% CI) = 0.37 (0.02; 0.72)] were observed in vascular stiffness. However, there were no notable differences in the D-D and nFMD parameters.ConclusionHIIT notably improved FIB, cfPWV, AIx, and FMD compared to MICT, or UC. Under certain conditions, PLT and AIx@75HR can also benefit from HIIT. It may be particularly advantageous for patients with cardiovascular disease.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/522614, identifier CRD42024522614.